DOMESTIC VIOLENCE: THE PROBLEM IS SOCIAL AND LEGAL - Xasanova Guzaliya Baxtiyorovna (Social science and innovation, 2023)
This article describes the main problems of domestic violence. We decided to choose this topic because it is very difficult to accept reality and often people, already realizing that something is going wrong, begin to deceive themselves with thoughts that everything is fine. Without stopping the negative attitude towards yourself in time, more serious consequences begin to occur. Considering reality, it is important to distinguish the statement of facts from interpretations. Only by our personal feelings can we understand whether our borders have been violated or not